ANALYSIS OF SOLAR ENERGY POTENTIAL TO ACHIEVE NEARLY ZERO ENERGY COMMUNITY. (CASE STUDY: MALIOBORO STREET, YOGYAKARTA). - Yuan, Anita; Ridwan, Mohammad Kholid; Setiawan, Bakti (Master in Systems Engineering, 2022)
A number of concrete strategies developed at global, national and local level as a step forward in implementing the sustainability in the community. An interesting concept introduced by the European Commission about buildings that can reach nearly zero energy building with energy efficiency and use the integration of renewable energy sources. This concept then developed into nearly zero Energy Community (nZEC) at community level referring to a group of buildings. Along with the vision of the Malioboro area in the RTBL Final Report on the creation of an environment-friendly and sustainable Malioboro area, research on the potential of solar energy as a PV power source is conducted.This study applies a mapping of the distribution of solar energy potential using 3D building data analysis on Open Street Map (OSM) and Digital Elevation Model (DEM). ArcGIS Pro software was applied to analyze 3D buildings data and geospatial aspects. This study shows a negative correlation between building density and the average solar energy potential with a coefficient of determination R2=0.85. Coverage Degree shows that only by using a solar energy conversion system, the level of coverage by renewable energy can be achieved from 10.25% – 12.56%. However, this value is not enough to achieve energy independence through the nearly Zero Energy Community (nZEC) concept, so a way is needed to achieve it in the future. Significant planning and geometric parameters in relation to performance indicators provide insight as a reference for establishing solar energy-friendly urban planning and architectural design guidelines.